2019
DOI: 10.1126/sciadv.aau4403
|View full text |Cite
|
Sign up to set email alerts
|

Seed predation increases from the Arctic to the Equator and from high to low elevations

Abstract: Alaska to Ecuador mega-experiment shows seeds are more likely to be munched toward the tropics and lowlands, as Darwin predicted.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 71 publications
(101 reference statements)
9
74
2
1
Order By: Relevance
“…A1H). We anticipated that predation risk would decline with elevation, as has been reported in many previous studies (de Mendoza and Catalan 2010; Roslin et al 2017;Moreira et al 2018;Hargreaves et al 2019). But survey data collected after the ex-periment was underway suggested that predator density was not strongly associated with elevation in our study area ( fig.…”
Section: Maladaptation On Steep Climate Gradients E69supporting
confidence: 51%
“…A1H). We anticipated that predation risk would decline with elevation, as has been reported in many previous studies (de Mendoza and Catalan 2010; Roslin et al 2017;Moreira et al 2018;Hargreaves et al 2019). But survey data collected after the ex-periment was underway suggested that predator density was not strongly associated with elevation in our study area ( fig.…”
Section: Maladaptation On Steep Climate Gradients E69supporting
confidence: 51%
“…Many studies have evaluated this "biotic interactions" hypothesis (sensu Schemske 9 ) by attempting to quantify latitudinal variation in the strength of species interactions. However, most of these studies have been limited in scale and have yielded mixed results, such that the generality of the biotic interactions hypothesis remains difficult to evaluate and controversial [5][6][7][14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…We recorded high levels of predation and seed removal, with levels of seed removal being higher than that recorded in a comparable tropical forest area (Hargreaves et al 2018). Similarly, levels of decomposition were high compared to litterbag experiments in forested and open landscapes (e.g.…”
Section: Discussionmentioning
confidence: 54%